Implementation Of Dashboard-Based Business Intelligence And Forecasting For Hiv/Aids Case Trend Analysis At Dr. M. Djamil Padang Hospital: A Case Study In The Period 2020–2025 To Improve The Quality Of Health Services And Data-Driven Prevention Program Planning - Firdaus; Marfalino, Hari; Wahyuni, Ritna (Riset Sinergi Indonesia (RISINDO), 2025)
This study aims to develop a Business Intelligence (BI) system using dashboards and forecasting to analyze HIV/AIDS case trends at RSUP Dr. M. Djamil Padang from 2015 to 2025. Given the increasing number of HIV/AIDS cases, a data-driven approach is essential for effective planning and decision-making. The methodology includes collecting historical HIV/AIDS case data, performing data cleaning and transformation (ETL), and constructing an interactive dashboard using BI platforms such as Tableau or Power BI. Additionally, statistical forecasting models are applied to predict future case trends. The results indicate that the developed BI dashboard effectively presents informative data visualizations, facilitates trend identification, and supports the planning of HIV/AIDS prevention and intervention programs. The forecasting models provide accurate predictions, aiding in resource allocation and evidence-based policy planning. In conclusion, implementing a BI system with dashboards and forecasting at RSUP Dr. M. Djamil Padang enhances the efficiency of monitoring and managing HIV/AIDS cases, thereby supporting more targeted decision-making in disease prevention and control efforts.